Ascorbic Acid Heterosis in Chili Peppers (Capisucm L.) - Sape Subba Tata, Owk Aniel Kumar, (Journal of Phytology, 2010)
Chili pepper is the most important world wide grown and consumed spice and vegetable crop because of its colour, taste, pungency, flavour and aroma. The nutritive value of chili pepper is largely determined by ascorbic acid content. The fruits at five ripening stages viz. M1, M2, M3, M4 and M5 from 18 parents and 40 F1 hybrids were analyzed for ascorbic acid content and per cent heterosis over mid and better parents. Among the parents and hybrids CA2 (208.0±0.68(M1), 231.0±0.66(M2), 280.0±0.31(M3), 253.0±0.34(M4) and 173.7±0.27(M5)) and H37 (211.0±0.45(M1), 248.6±0.32(M2), 298.0±0.35(M3), 272.3±0.70(M4) and 188.0±0.17(M5)) showed higher ascorbic acid content (mg/100g) FW. Hybrid H27 (CA25XCA10) manifested highest per cent heterosis over mid parent (92.34%) and better parent (79.32%) respectively. The results revealed that ascorbic acid content increased from green to red while, decreased in red partially dried and red fully dried fruits. Crosses H37, H27, H25, H26, H36, H35 and H31 were best for ascorbic acid content and per cent heterosis over mid and better parents could be suggested for further evaluation programmes to develop chili pepper varieties with good nutritive values.